Mediator Effects of Cognitive Load on Association between Self-Efficacy and Task Load in Intensive Care Unit Nurses. - Tingting, P.; Xun, D.; Jun, W.; Shu, D.; Shan, Z. (Journal of Nursing Management, 2024)
Aims. To explore the mediating effect of cognitive load on the relationship between self-efficacy and task load among intensive care unit (ICU) nurses. Background. Studies related to ICU nurses' self-efficacy, cognitive load, and task load are noteworthy but limited. Methods. A total of 253 ICU nurses from three tertiary hospitals in Beijing were recruited and investigated by the Chinese version of the National Aeronautics and Space Administration-Task Load Index (NASA-TLX), General Self-Efficacy Scale (GSES), and an instrument for Measuring Different Types of Cognitive Load (MDT-CL) scales. SPSS 25.0 was used for Pearson correlation analysis and multiple linear regression analysis and mediation effect analysis using Model 4 in PROCESS (5,000 resamples). Results. Mediation analysis indicated that a partial mediating effect of extraneous cognitive load between self-efficacy and task load among ICU nurses was −0.707 (95% CI: −0.940, −0.504), accounting for 51.64% of the total effect. Conclusion. This study suggests that enhancing ICU nurses' self-efficacy can be a potential strategy to decrease extraneous cognitive load and task load. Implications for Nursing Management. Nursing administrators should actively implement intervention strategies based on influencing the task load pathway of ICU nurses to ensure they can provide safe and high-quality nursing services.